AVALIAÇÃO DA SATISFAÇÃO DOS USUÁRIOS EM HIS EM GOIÂNIA - Arantes, Analu Guimarães; Abreu – Harbich, Loyde Vieira de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The main objective of this research is to show if the architectural typology, superimposed house, presents positive indexes of user satisfaction, in relation to thermal comfort and adaptability. The research is structured in the survey of data of perception of the users, and, for this, the following methodologies were adopted: structured observation and research form. The Residencial Buena Vista III (2013), was adopted as a case study, due to the adoption of the architectonic typology overlapping house and the building block system selfsupporting concrete. As main results, it has been that the building does not offer suitable spaces for activities related to reading and leisure. In addition, the environments with the highest negative evaluation indices are: service area, kitchen and living room. In terms of thermal comfort, maiotes dissatisfaction takes place during the months of July and September, and that the kitchen is the environment that offers less thermal comfort conditions.